The Analysis of Worker Safe Behaviour based on the Antencendent Behaviour Consequence (ABC) Behaviour Model - Anugrah Visar Rahman; Endang Dwiyanti (Universitas Airlangga, 2020)
Introduction: PT. Kreasindo Wira Darma is an electrical construction company offering substation and electrical transmission installation in Indonesia. The common basic cause of work accident is unsafe behaviour and unsafe condition. This research aimed to analyze the safe behaviour of construction workers at Blimbing substation using behaviour-based safety approach and Antencendent, Behaviour, Consequence (ABC) theory. Method: This research was an observational descriptive study using cross-sectional design. The data were collected using questionnaire, observation, and interview. There were a total of 20 construction workers at PT. Kreasindo Wira Darma which became the respondents for this study, and total population was used as the samples. This study’s variables include antencendent and consequence as independent variables and worker’s safe behaviour as the dependent variable. Results: most of construction workers had good knowledge by 90%, good awareness by 90%, all workers have good motivation and fulfilled need for safety by 100%, 18 workers said that there were Occupational Health Safety (OHS) rules in effect at the company by 90%, and workers said that they have received rewards/praises and punishments by 95%. Results also showed that most cosntruction workers have applied safe behaviour at the workplace. Conclusion: Workers will consistently practice safe behaviour when they are equipped with knowledge, awareness, good motivation, compliance with Occupational Health Safety (OHS) rules, and are given reward and punishment. Keywords: behavior-based safety, electrical construction, safe behaviour